Prarancangan Pabrik Asam Nitrat Dari Asam Sulfat dan Natrium Nitrat Kapasitas 65.000 Ton Per Tahun - Pratiwi, Luluk; , M. Mujiburohman, Ph.D; , Hamid Abdillah, S.T., M.T (2016)
Nitric acid plant with raw materials of sulphuric acid and sodium nitrate with a capacity 65.000 tons/year is planned to be established in 2020 in Karawang, West Java. The sodium nitrate is imported from Chile and the sulphuric acid is from PT Indonesian Acid Industry. The nitric acid production uses continuous stirred tank reactor (CSTR). The reaction is exothermic, non adiabatic, and irreversible, carried out at temperature of 150°C and pressure of 1 atm. The plant is categorized as low risk process due to the friendly operating conditions. The process of nitric acid production is initiated with reacting sulphuric acid and sodium nitrate in the reactor. The vapor product of reactor is condensed by a partial condenser and is purified in distillation tower to produce nitric acid with purity of 98%, while the liquid product, called niter cake, is stored as side product. Based on the capacity, the production of nitric acid is 8,207.0707 kgs/hour. To support the process, utilities are required including 264,779.5449 kgs/hour of cooling water, 19,772.5449 kgs/hour of steam. Which is obtained from boiler consuming fuel oil as much as 1,473.8109 L/hour, and electricity supplied from PLN and generator set. The water source is taken from Kalimalang river,. The economic analysis gives the profit before tax is Rp113,168,435,407/year, and Rp84,876,326,556/year after tax. The percent Return on Investment (ROI) before tax is 34.52% and 25.89% after tax. The Pay Out Time (POT) before tax is 2.25 years and 2.79 years after tax. The Break Event Point (BEP), the Shut Down Point (SDP), and the Internal Rate of Return (IRR) are 47.80, 25.11%, and 40.27%, respectively. The above economic analysis concludes that the plant is feasible to set.